Irrigação e aplicação de fungicida na ocorrência de doenças e produtividade do girassol - Maldaner, Ivan Carlos (2009)
The occurrence of disease has been one of the main problems of the sunflower crop over the years. The objective of this study was to evaluate the effect of irrigation and the application of fungicides on the occurrence of diseases and yield of achenes of two genotypes of sunflower crop in the main and second crop season in the central region of Rio Grande do Sul. The experiments were carried out at Plant Science Department of the Federal University of Santa Maria, Santa Maria, RS, Brazil during the main season at 2007 and the second crop season of 2008. Following growth and development of plants during the crop season through phenometrical and phenological observations. The meteorological data were collected in the center of the experimental area with an automatic weather station and psychrometric pairs at different levels. Twelve treatments were used arranged in a completely randomized design with four replications. The treatments consisted of irrigated and non irrigated controls and different forms of protection with fungicide according to the accumulated severity values (SV) estimated by the FAST (VS = 16, 22, 28) without irrigation and with irrigation and protection with fungicide with 16 VS. The theoretical values of severity (VS) were calculated using the FAST system, considering the duration of the period with relative humidity greater than 90% and air temperature during this period. When the values of the severity of the treatment were achieved the fungicide was applied, and a new count of VS began. The progress of the disease was analyzed based on weekly observations of the severity of the symptoms of the disease in three plants per plot. It was found that irrigation increases the productivity of achenes of sunflower cultivation in the main season, provided that weather conditions are not favorable for the occurrence of the alternaria blight and Septoria leaf blight, or that fungicides to control these diseases are applied before flowering. In the second crop season the effect of irrigation on yield of achenes is negative due to higher occurrence of the alternaria blight and Septoria leaf blight in sunflower. The prediction of the occurrence of diseases in sunflower can be made from weather elements, but adjustments are needed to define the most appropriate criteria.